Negotiating evangelicalism and pentecostalism: Global entanglements, identity politics and the future of pentecostal studies - Maltese, Giovanni; Bachmann, Judith; Rakow, Katja (PentecoStudies, 2019)
Pentecostal studies seems to be caught in a deadlock with regard to its subject matter of research. Most definitions of Pentecostalism appear either too broad or too narrow compared with the inclusive sense in which “Pentecostalism” is used in academia. Scholars admit that Pentecostal is a “fuzzy category”, but still, they opt for a combination of essentialist definitions, rarely investigating whether their empirical data could open up fresh perspectives on how to conceptualize the subject matter of Pentecostal studies. Others postulate a “Pentecostalization” of Christianity and/or tend to dissolve Pentecostal studies into the study of Evangelicalism and/or Catholicism for other reasons. Still others prefer to speak of Pentecostalisms in the plural or seem to have given up on finding a consensus. The introduction to this special issue proposes an alternative approach. Drawing on Michael Bergunder's work, it suggests to conceptualize Pentecostalism as a name that keeps together various equivalential chains. As the articles collected in this special issues show, this means to investigate the meaning “Pentecostalism” assumes in specific research contexts as product of local identity politics and analyse its entanglement in a global discourse about “Pentecostalism”.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Antagonism; Discourse; Equivalential chains; Evangelicalism; Global entanglements; Hegemony; Identity politics; Knowledge production; Local negotiations; Pentecostal studies